Suppression of systemic lupus erythematosus in NZBWF1 mice infected with Hymenolepis microstoma. (June 2020) - Olia, Alex; Shimokawa, Chikako; Imai, Takashi; Suzue, Kazutomo; Hisaeda, Hajime
Abstract: Intestinal helminths induce immune suppressive responses thought to regulate inflammatory diseases including allergies and autoimmune diseases. This study was designed to evaluate whether helminthic infections suppress the natural development of systemic lupus erythematosus (SLE) in NZBWF1 mice. Infection of NZBWF1 SLE-prone mice with two nematodes failed to establish long-lasting settlement. However, the Hymenolepis microstoma (Hm) rodent tapeworm successfully established long-term parasitization of NZBWF1 mice and was used to evaluate the suppressive effects of helminth infection. Ten-month-old NZBWF1 mice developed symptoms including autoantibody generation, proteinuria, glomerular histopathology, and splenomegaly, but mice infected with Hm at 2 months of age did not show any clinical signs. Furthermore, infection with Hm reduced lymphocyte activation and increased regulatory T cells in the spleen and mesenteric lymph nodes. These results indicate that infection with Hm protects NZBWF1 mice from naturally developing SLE and suggest that pathological immunity is attenuated, presumably because of the induction of regulatory T cells. Graphical abstract: Unlabelled Image Highlights: SLE-prone NZBWF1 mice were refractory to Hp and Tm but susceptible to Hm. Hm prevents natural development of SLE and prolonged survival of NZBWF1 mice Hm infection increases Tregs and decreased plasma cells and Tfh in NZBWF1 mice.